Asuhan Keperawatan pada Ny. M dengan Diagnosa Ulkus Diabetikum Menggunakan Penerapan Intervensi Slow Deep Breathing dalam Mengurangi Kecemasan di Rumah Sakit Az-Zahra - Ardha Pangestu; Hardono Hardono (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
The prevalence of diabetic ulcers in Indonesia reaches 12-15% of all sufferers. This condition has an impact on the patient's psychological condition in the form of anxiety due to wounds that are difficult to heal, changes in body image, and concerns about the possibility of amputation. One of the nonpharmacological interventions that can help overcome anxiety is the slow deep breathing technique. The purpose of writing this scientific paper is to carry out Nursing Care for Mrs. M with Diagnosis of Diabetic Ulcers using the application of slow deep breathing intervention in reducing anxiety at Az-Zahra Hospital. The writing method is a nursing care process that includes the stages of study, nursing diagnosis, planning, implementation, and evaluation. The subject of care was Mrs. M, a patient with diabetic ulcers in the inpatient room of Az-Zahra Hospital. Data collection was carried out through interviews, observations, documentation studies, and physical examinations, and using a medical-surgical nursing care assessment format. The ethical principles applied use the principles of Nursing Ethics. The results of nursing care showed that after three days of slow deep breathing intervention, patients reported feeling calmer, sleeping better, and anxiety levels decreased from moderate to mild based on observation results and anxiety scales used. This suggests that slow deep breathing interventions are effective in helping to reduce anxiety in patients with diabetic ulcers. It is hoped that patients and families can continue these breathing exercises independently as part of stress management efforts and quality of life improvement.